How rigid business approaches paved the way for inclusive business practices: A case study of innovative milk trading practices aligned with pastoralists - Kihoro, Esther; Crane, Todd A.; Lupatu, Habib; Vellema, Sietze (Informa UK Limited, 2024)
The poor integration of pastoral households into milk markets has been attributed to several aspects, including the mobile nature of pastoralists and seasonal fluctuations in milk volumes. Pastoralists also keep their cattle as a store of wealth, meaning they are keener to increase livestock numbers than their productivity. These aspects make it risky for traders to source milk from pastoral households because of the high transaction costs and the uncertainty of milk prices and volumes. This study evaluates the practice of sourcing milk and the innovative strategies used by several traders to ensure that pastoral households are integrated into milk markets. Methodologically, we use the practice approach, where practices are meaning-making and order-producing activities that result in an institutionalised way of doing. The results indicate that previous market engagement for pastoralists took place in a rigid, predetermined context that failed to account for pastoralists’ varying production practices. Our analysis shows how the skillful performance of traders and motorbike milk aggregators has aligned with the logic and interests of pastoralists. However, this alignment capacity can only be realised under specific conditions, which involve aligning with local production systems, coordinating with intermediaries, and having a flexible approach to marketing prices and buyers across seasons. This study highlights that economic organization emerges from everyday action and problem-solving and is not only an outcome of an intentional system design. In doing so, this study contributes to more realistic needs-driven business intervention strategies that are beneficial in achieving inclusive rural development.